Pengaruh Earning Per Share terhadap Harga Saham pada Perusahaan Sektor Batu Bara di Indonesia Periode 2022-2024 (Jurnal Ekonomi Bisnis dan Akuntansi, 2024)
The Indonesian coal sector will experience large fluctuations during the 2022–2024 period due to changes in global coal prices and post-pandemic economic conditions. This movement has an impact on company value and the share price of coal issuers, so it is important for investors to understand the fundamental factors that have an influence on share prices. This study has a tendency to analyze the influence of earnings per share on share prices in companies operating in the coal sector that are officially registered on the IDX. The method used is quantitative. The population uses coal sector companies in Indonesia for the 2022-2024 period with a population of 30 companies. From a population of 30 companies, only 16 sample companies met the characteristics. The results of the study show that EPS has a positive influence and has significance on share prices, so that an increase in earnings per share can be proven to act as a main indicator that can be paid attention to by parties investing in efforts to assess and prospect for coal companies.